(untitled) (International Journal of Physiotherapy, 2017)
Background: In this study, was to evaluated the effectiveness of motor task and cognitive task interference while walking to improve gait parameters of subjects with Parkinson’s disease. Methods: In this Randomized Controlled trial, 30 subjects with Parkinson’s disease of age group between 50and 70 years randomly divided into two groups. The first group had motor task interference, and the second group had calculation task interference while walking along with conventional physical therapy. Gait parameters recorded as outcome measures. Both the groups received 1-hour training for three weeks for one month. Results: As per the paired t-test values, there was significant (p<0.001) improvement in the gait parameters for both the group’s pre and post training. Motor task interference showed better improvements than calculation-task interference group among subjects with Parkinson’s disease in all the gait parameters measured with a p-value less than 0.001. Conclusion: To improve the gait parameters for mild to moderately disabled patients with Parkinson’s disease, the dual task training by using motor task while gait training along with conventional Physical Therapy will be more useful than using cognitive task.